2017
DOI: 10.14740/jcgo446w
|View full text |Cite
|
Sign up to set email alerts
|

Serous Endometrial Intraepithelial Carcinoma: Case Report and Literature Review

Abstract: Serous endometrial intraepithelial carcinoma (SEIC) is a rare but highly aggressive form of uterine endometrial cancer. We present a case of a premenopausal 42-year-old patient who presented with copious vaginal bleeding without a specific medical history. A total abdominal hysterectomy was performed. Pathologic results showed SEIC. We report this case and include a brief literature review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Serous endometrial intraepithelial carcinoma (SEIC), a malignant lesion associated with p53 mutation in a background of atrophic endometrium, has been postulated to be a precursor of uterine serous carcinoma [ 44 , 45 ]. SEIC has been identified in 40–89% of patients diagnosed with serous endometrial cancer [ 46 , 47 , 48 , 49 ]. Furthermore, concordant genetic mutations have been demonstrated in both components of SEIC and serous endometrial cancer [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Serous endometrial intraepithelial carcinoma (SEIC), a malignant lesion associated with p53 mutation in a background of atrophic endometrium, has been postulated to be a precursor of uterine serous carcinoma [ 44 , 45 ]. SEIC has been identified in 40–89% of patients diagnosed with serous endometrial cancer [ 46 , 47 , 48 , 49 ]. Furthermore, concordant genetic mutations have been demonstrated in both components of SEIC and serous endometrial cancer [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 46 of 81 patients, there was no evidence of disease at the end of follow-up, 12 patients were alive with the disease, 18 patients died from the disease and 2 patients died from other causes. In two studies, 62.5% and 33.3% of patients receiving adjuvant chemotherapy, respectively, relapsed [2,10], while, in three studies, none of the patients relapsed [3,12,14]. Among patients not receiving any adjuvant treatment, only in one study were no relapses reported [13], and the average recurrence rate was 28.78%, ranging from 16.6% to 100%, and the DFS was 59.1%.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, although the benefits of adjuvant treatments are not yet clear [21,22], it appears necessary to opt for additional treatments or close follow-up in patients who have undergone incomplete surgical staging. Adjuvant treatments were adopted in most cases in patients with advanced stages of the disease, except for one study in which the more aggressive approach could be justified by the young age of the patient examined, albeit with stage IA disease [12]. The patients who were followed had promising results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sherman et al 4 and Kawata et al 13 suggested that EIC was the major precursor of serous endometrial carcinoma seen in 100 per cent of ESC with concurrent EIC. In the present study, we observed 48 out of 120 patients with EIC in the adjacent endometrium as well as five cases of non-invasive carcinoma.…”
Section: Discussionmentioning
confidence: 99%